Levels of Physical Activity in Portuguese Children: the Impact of the Covid-19 Pandemic - Cristiana Mercê; Jéssica Cordeiro; Catarina Romão; Marco Branco; David Catela (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Portuguese children spend about eight hours/day in sedentary behaviours, presenting only one hour in active play. This inactivity rate is about 84%. The lower levels of physical activity (PA) trigger several health problems in children and, after, in adulthood. With the appearance of the pandemic of COVID-19 and, consequently, increase of confined tasks like distance learning, has been verified the PA decrease and screen and sedentary behaviours increase in children. The objectives are: i) verify PA levels; ii) compare PA levels between genders, before and during the pandemic. The questionnaire “Cuestinário Pictórico de la Actividad Físca Infantil” has been translated and applied in Portugal, across the platform Google Forms, having been answered by 61 children of average age of 12.0±3.1 years. Before the pandemic, male children practice more PA. During the pandemic, has been verified a practise decrease in both genders. The PA levels settled between “Little active” and “Nothing active”, not checking differences between genders. The child’s age affected positively the formal PA in academies and clubs and, negatively the informal practise. It has been verified that lower PA levels are associated with higher weight values. Portuguese children PA levels are well below the recommended, situation that worsened during the pandemic. In order to combat childhood inactivity and overweight, it is necessary to develop measures to promote PA early specially in situations of pandemic and/or confinement, in which PA reaches even lower levels.